A Comparative Study of the Use of Cow's Milk and Plant-Based Alternatives Such as Almond Milk and Oat Milk on Diabetic Rats - Ashkanani, Rasha (International Journal of Food Sciences, 2023)
Purpose: The present study was conducted to evaluate physicochemical, rheological, microbiological, antioxidant and sensory properties of caw, almond and oat milk. Caw milk served as a control (animal source), and the other treatments were made from almond milk and oat milk (plant source). Methodology: Thirty five male adult albino rats of Sprague Dawely strain weighing 180- 220 g were divided into 5 groups as follows: Group (1) non-treated non- diabetic rats (negative control). Group (2) diabetic rats (received Streptozotocin (STZ), 60 mg/Kg BW) (positive control).Group (3) diabetic rats fed on basal diet with caw milk (10g/day) by epi gastric tube. Group (4) diabetic rats fed on basal diet with almond milk (10g/day) by epi gastric tube. Group (5) diabetic rats fed on basal diet with oat milk (10g/day) by epi gastric tube. Results: Results revealed that almond milk were more effective in increasing the dry matter, protein, ash, fiber, carbohydrate, energy, acidity, viscosity, phenolic content and antioxidant activity. Almond milk had the highest scores for sensory properties compared to other milk treatments. The Almond milk was evaluated as hypoglycaemic agent streptozotocin-induced diabetic rats. The treatment of diabetic rats with almond milk showed a significant decreases(p<0.001) in levels of blood glucose, malondialdehyde (MDA), low density lipoprotein (LDL), cholesterol (CL), triglyceride (TG), AST, ALT , ALP, creatinin and urea and increased (p<0.001) high density lipoprotein (HDL) and total protein and albumin in comparison to diabetic rats. Unique Contribution to Theory, Practice and Policy: This study indicates that the theory used in the study has been validated. Consumption of almond milk in diabetic rat groups caused significant improvement in all these factors, compared to the positive control group (untreated diabetic rats), indicating that almond and oat milk can play a preventive role in such patients. It can be used as an indicator to establish future studies on the importance of consuming plant-based alternatives to milk, such as almond milk and oat milk. Policy makers should recognize the importance of a balanced diet for health in which plant-based alternatives are available and reflect this in public health recommendations.